Studi Komparatif Kebijakan Pemerintah Jepang Dan Indonesia Dalam Ekonomi Dan Industrialisasi - Lestari, Lina Puji (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2025)
Economic policies and industrialization are important factors in the development of a country. This study compares the policies of the Japanese government after World War II and Indonesia after independence, analyzing the policy achievements of both countries as well as identifying the factors that influence government policies during development. This study uses a qualitative comparative method with a literature review approach. Data and information are collected from many secondary sources, such as books, journal articles, research papers, and publications from governments and international organizations. The results of the study found that Japan adopted a